THE EFFECT OF TRUST AND SERVICE QUALITY ON THE SAVINGS DECISIONS OF MILLENNIALS AND ITS IMPLICATIONS FOR STRENGTHENING THE DIGITALIZATION STRATEGY OF RURAL CREDIT BANKS IN WEST JAVA - Aripin, Zaenal; Suteja, Jaja (Jurnal Riset Bisnis dan Manajemen, 2026)
This study investigates what compels millennial customers in West Java to save with Rural Banks (Bank Perekonomian Rakyat). By analyzing data from nearly 200 respondents, the research isolates the comparative impact of institutional trust versus service quality on financial decision-making. The results offer a compelling strategic insight: while trust is a fundamental baseline, service quality is the dominant driver, wielding a significantly stronger influence on saving behavior. Specifically, millennials prioritize reliability and digital convenience over traditional reputation alone. Together, these two factors account for 58% of a customer's decision to save. For Rural Banks, the managerial implication is clear. To capture this demographic, institutions must evolve beyond legacy relationships and aggressively enhance digital capabilities and transparency. Long-term competitiveness relies on blending the integrity of community banking with the seamless efficiency of modern service.